(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
This study aims to analyze the role of costumer satisfaction in mediating the influence of product quality and brand image on repurchase intention in Nike shoe products. Using a quantitative approach and Structural Equation Modeling method based on Partial Least Squares (SEM-PLS), this study collected data from 100 Nike costumer respondents in Indonesia who had made purchases in the past two years. The results show that product quality has a significant positive influence on costumer satisfaction, while brand image contributes more strongly to the emotional dimension of satisfaction. Costumer satisfaction has been shown to mediate the relationship between product quality and brand image and repurchase intention. These findings underscore the relevance of the Expectancy-Disconfirmation Theory in explaining costumer behavior, while providing managerial implications for Nike to balance quality strategies and brand image to strengthen costumer loyalty.